Virtual assistants in customer interface - Hiltunen, Samuli (My University, 2022)
This thesis covers use of virtual assistants from a user organization’s perspective, exploring challenges and opportunities related to introducing virtual assistants to an organization’s customer interface. Research related to virtual assistants is spread over many distinct fields of research spanning several decades. However, widespread use of virtual assistants in organizations customer interface is a relatively new and constantly evolving phenomenon. Scientific research is lacking when it comes to current use of virtual assistants and user organization’s considerations related to it. A qualitative, semi-systematic literature review method is used to analyse progression of research related to virtual assistants, aiming to identify major trends. Several fields of research that cover virtual assistants from different perspectives are explored, focusing primarily on Human-Computer Interaction and Natural Language Processing. Additionally, a case study of a Finnish insurance company’s use of virtual assistants supports the literature review and helps understand the user organization’s perspective. This thesis describes how key technologies have progressed, gives insight on current issues that affect organizations and points out opportunities related to virtual assistants in the future. Interviews related to the case study give a limited understanding as to what challenges are currently at the forefront when it comes to using this new technology in the insurance industry. The case study and literature review clearly point out that use of virtual assistants is hindered my various practical challenges. Some practical challenges related to making a virtual assistant useful for an organization seem to be industry-specific, for example issues related to giving advice about insurance products. Other challenges are more general, for example unreliability of customer feedback. Different customer segments have different attitudes towards interacting with virtual assistants, from positive to negative, making the technology a clearly polarizing issue. However, customers in general seem to be becoming more accepting towards the technology in the long term. More research is needed to understand future potential of virtual assistants in customer interactions and customer relationship management.

Tämä tutkielma tutkii virtuaaliassistenttien käyttöä käyttäjäorganisaation perspektiivistä, antaen käsityksen mitä haasteita ja mahdollisuuksia liittyy virtuaaliassistenttien käyttöönottoon organisaation asiakasrajapinnassa. Virtuaaliassistentteihin liittyvä tutkimus jakautuu monien eri tutkimusalojen alaisuuteen ja useiden vuosikymmenien ajalle. Laajamittainen virtuaaliassistenttien käyttö asiakasrajapinnassa on kuitenkin verrattain uusi ja jatkuvasti kehittyvä ilmiö. Tieteellinen tutkimus joka liittyy virtuaaliassistenttien nykyiseen käyttöön ja käyttäjäorganisaation huomioon otetaviin asioihin on puutteellista. Tämä tutkielma käyttää kvalitatiivista, puolisystemaattista kirjallisuusanalyysimetodia tutkiakseen virtuaaliassistentteihin liittyviä kehityskulkuja, tarkoituksena tunnistaa merkittäviä trendejä. Tutkimus kattaa useita tutkimusaloja jotka käsittelevät virtuaaliassistentteja eri näkökulmista, keskittyen pääasiassa Human-Computer Interaction- sekä Natural Language Processing -tutkimusaloihin. Lisäksi tutkielmassa on tapaustutkimus suomalaisen vakuutusyhtiön virtuaaliassistenttien käytöstä, joka tukee kirjallisuusanalyysiä ja auttaa ymmärtämään käyttäjäorganisaation perspektiiviä. Tutkielma kuvailee kuinka keskeiset teknologiat ovat kehittyneet, auttaa ymmärtämään tämänhetkisiä ongelmia jotka koskettavat organisaatioita sekä esittelee virtuaaliassistentteihin liittyviä mahdollisuuksia tulevaisuudessa. Tapaustutkimukseen liittyvät haastattelut antavat rajoitetun kuvan kyseisen uuden teknologian käyttöön liittyvistä haasteista vakuutusalalla. Tapaustutkimus ja kirjallisuusanalyysi osoittavat että virtuaaliassistenttien käyttöönottoon liittyy erilaisia käytännön haasteita. Jotkut haasteet vaikuttavat olevan toimialakohtaisia, liittyen esimerkiksi vakuutustuotteita koskeviin neuvoihin. Toiset haasteet taas ovat yleisempiä, liittyen esimerkiksi asiakaspalautteen epäluotettavuuteen. Eri asiakassegmenteillä on erilaisia asenteita virtuaaliassistentteja kohtaan, vaihdellen positiivisesta negatiiviseen, joten kyseinen teknologia on selvästi polarisoiva aihe. Pitkällä aikavälillä asiakkaiden asenteet teknologiaa kohtaan vaikuttavat kuitenkin muuttuvan hyväksyvämpään suuntaan. Lisää tutkimusta tarvitaan jotta voidaan ymmärtää virtuaaliassistenttien tulevaisuuden potentiaalia asiakaskohtaamisissa ja asiakkuudenhallinnassa.
Keywords: virtual assistant, chatbot, customer interface, insurance